Inorganic Nanoparticle-Loaded Exosomes for Biomedical Applications - Taraneh Barjesteh; Shomit Mansur; Yuping Bao (Molecules, 2021)
Exosomes are intrinsic cell-derived membrane vesicles in the size range of 40–100 nm, serving as great biomimetic nanocarriers for biomedical applications. These nanocarriers are known to bypass biological barriers, such as the blood–brain barrier, with great potential in treating brain diseases. Exosomes are also shown to be closely associated with cancer metastasis, making them great candidates for tumor targeting. However, the clinical translation of exosomes are facing certain critical challenges, such as reproducible production and in vivo tracking of their localization, distribution, and ultimate fate. Recently, inorganic nanoparticle-loaded exosomes have been shown great benefits in addressing these issues. In this review article, we will discuss the preparation methods of inorganic nanoparticle-loaded exosomes, and their applications in bioimaging and therapy. In addition, we will briefly discuss their potentials in exosome purification.